Integrated analysis of multi-omics data for the discovery of biomarkers and therapeutic targets for juvenile idiopathic arthritis - Yi-Xin Cai; Xiao-Li Chen; Dai-Shan Zheng; Yue-Zhong Huang; Zhan-Pei Bai; Xiu-Feng Huang (Journal of Translational Autoimmunity)
Background: Juvenile idiopathic arthritis (JIA) is a prevalent chronic rheumatic disease affecting children. Current medications merely alleviate symptoms rather than curing the disease. Hence, the identification and development of novel drug targets and biomarkers for JIA are imperative for enhancing treatment efficacy. Methods: We employed two-sample Mendelian randomization (MR) analysis to investigate the causal effects of plasma proteins on JIA. Additionally, colocalization, bulk RNA-seq, and single-cell RNA-seq analyses were conducted to further investigate and validate the potential of candidate proteins as drug targets. Results: Through MR analysis, we successfully identified five plasma proteins that are causally linked to JIA. Genetically inferred lower levels of AIF1, TNF, and TNFSF11 were associated with an elevated risk of JIA, while higher levels of AGER and GP1BA proteins were positively correlated with JIA risk. Colocalization analysis further supported our findings on GP1BA (OR = 9.26, 95 % CI: 2.30–37.20) and TNFSF11 (OR = 0.18, 95 % CI: 0.07–0.45). Based on this evidence, we classified these five proteins into two tiers. Finally, we conducted a systematic evaluation of the druggability and current drug development progress for these identified candidate proteins. Conclusions: This study employed MR analysis to reveal causal relationships between plasma proteins and JIA, identifying five potential candidate proteins as promising drug targets for JIA, particularly focusing on GP1BA and TNFSF11.